Public spending efficiency and economic growth: the moderating roles of value-added tax and country governance - Chan, Sok Gee; Ramly, Zulkufly (2015)
This study examines the impact of government spending efficiency on the economic growth of 115 countries with value-added tax (VAT) system. We seek to examine the moderating role of the VAT system and country governance in the relationship between public spending efficiency and the economic growth of a nation. The sample covers the period between 1984 and 2014. Using GMM estimation based on two-step estimate, we found (1) government spending efficiency enhances economic growth, (2) an efficient as well as transparent tax administration and higher tax revenue generated from the VAT system enhances the effect of an efficient government spending on the economic growth of a country and (3) the moderating role of the VAT system is further enhanced by the quality of democracy and legislative strength of the government.